2021
DOI: 10.1136/bmjopen-2021-050565
|View full text |Cite
|
Sign up to set email alerts
|

Is Indonesia achieving universal health coverage? Secondary analysis of national data on insurance coverage, health spending and service availability

Abstract: ObjectivesTo analyse the relationship between health need, insurance coverage, health service availability, service use, insurance claims and out-of-pocket spending on health across Indonesia.DesignSecondary analysis of nationally representative quantitative data. We merged four national data sets: the National Socioeconomic Survey 2018, National Census of Villages 2018, Population Health Development Index 2018 and National Insurance Records to end 2017. Descriptive analysis and linear regression were performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
38
0
11

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 33 publications
2
38
0
11
Order By: Relevance
“…An investigator stated that financial problems cause late presented AA [3] . However, that reasons was not found in this study, presumably due to high coverage (83.5%) of national healthcare insurance [18] , [19] , facilitating Indonesian citizens' access to healthcare facilities.…”
Section: Discussionmentioning
confidence: 63%
“…An investigator stated that financial problems cause late presented AA [3] . However, that reasons was not found in this study, presumably due to high coverage (83.5%) of national healthcare insurance [18] , [19] , facilitating Indonesian citizens' access to healthcare facilities.…”
Section: Discussionmentioning
confidence: 63%
“…A subsequent systematic review found many studies reporting positive impact of PFHI, though it also reported studies showing poor impact [ 45 ]. In the South Asian and South East Asian context, recent studies from India, Indonesia, Vietnam and Philippines have shown that increasing population coverage under PFHI has not been effective in protecting the people from high OOPE [ 46 , 47 ]. The need of offering financial protection to the population is most evident in these nations but so is the limited success in achieving it.…”
Section: Discussionmentioning
confidence: 99%
“…A key feature of Indian PFHI is its reliance on for-profit private hospitals for delivery of services. This is a feature that seems to be common in countries with poorly effective PFHI like India and Indonesia [ 42 , 47 ]. Further research is recommended to examine this aspect in depth in LMIC contexts.…”
Section: Discussionmentioning
confidence: 99%
“…The VAS and WOMAC scores evaluation were conducted on the treated knee to avoid bias. 22 Prolotherapy -proliferative therapy -has been reported to be an effective method to treat musculoskeletal and joint diseases. 23 Although the mechanism is still unclear, Rabago et al concluded that prolotherapy provokes mild inflammation and cell stress in the weakened ligament or tendon area.…”
Section: Discussionmentioning
confidence: 99%